KARAKTERISTIK MORFOMETRIK DAN HABITAT KIJING TAIWAN (Sinanodonta woodiana) DI ALIRAN IRIGASI DESA SAMBORA KECAMATAN TOHO KABUPATEN MEMPAWAH - Fitri Nurleha; widadi padmarsari soetignya; Sri Rahayu (Jurnal Sains Pertanian Equator, 2020)
Sinanodonta woodiana is known as kijing taiwan which is mostly found in the irrigation flow of the village of Sambora Toho District Mempawah Distric. However, its existence is now experiencing a decline. For this reason, management is needed that requires data on morphometric and habitat characteristics. Therefore the purpose of this study was to determine the morphometric characteristics and habitat characteristics of S. woodiana in the irrigation flow of Sambora Village, Toho District, Mempawah Regency. The research method used was Purposive Random Sampling, using three different observation stations, namely station 1 is in the upstream part of the irrigation area close to a waterfall of oil palm plantations and freshwater fish cultivation ponds, station 2 is in an area adjacent to freshwater fish cultivation ponds and settlements, and station 3 is in a downstream area close to factory waste disposal tofu, freshwater fish farming ponds, and oil palm plantations.This research was conducted in March - May 2020 in the irrigation flow of Sambora Village, Toho District, Mempawah Regency. Based on the results of the study, there were 565 individuals of S. woodiana. All characters of mean shell length (PC), shell height (TC), shell thickness (TBL), and total weight (BT) show that the size varies between male and female sex, the female sex is greater than the male sex. The density values ranged from 0.37 to 3.02ind / m2. The density between stations is different and the highest is at station I and the lowest is at station III. Keywords: S. woodiana, Morphometric, Density.